PENINGKATAN KEMAMPUAN MEMBACA NYARING MENGGUNAKAN MEDIA CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA UNTUK PESERTA DIDIK KELAS III SD NEGERI NAIKOTEN 2 KOTA KUPANG - Sampe, Markus; Djawa, Alex; Bukifan, Maria Cresensia (Journal of Character and ELementary Education, 2024)
The present research aimed to enhance the ability of class III students at SD Negeri Naikoten 2, Kupang city, to ready aloud by using picture story media. The research methodology employed in this study was Classroom Action Research (CAR), which consisted of four stages: planning, implementation, observation, and reflection. The study included 18 stundents from class III-B of SD Negeri Naikoten 2, Kupang city, comprising 9 female and 9 male stundents. The data collection process employed test, observation, and documentation techniques, and the collection data was analyzed using quantitative data analysis techniques. The result of the first cyle test assessment revealed that 14 students (78%) had completed it, while the other 4 students (22%) had not completed it. In cyle II, 16 students (89%) completed the test, while 2 students (11% ) did not. The study found that using picture story media improved students reading-aloud skills and enhanced their accuracy, pronunciation, intonation, fluency, and loudness. Hence, it can be concluded that using picture story media can improve the ability to read aloud in Indonesian language subjects for class III students at SD Negeri Naikoten 2, Kupang city.